Comparative study of hospital stay duration among cesarean section patients using ERACS and conventional care in Lampung, Indonesia - Anita Anita; Muhammad Abduh Musyaffa (International Journal of Public Health Science (IJPHS), 2026)
This study is important to evaluate the impact of the effectiveness of the enhanced recovery after cesarean section (ERACS) method compared to conventional care on the length of hospital stay in cesarean patients in Lampung, Indonesia, considering the increasing number of cesarean sections and the need to optimize patient recovery and reduce care costs. This research is a quantitative study using a retrospective observational design. The total population was 210, with 102 samples (51 ERACS groups: 51 conventional groups) taken using purposive sampling. The research was conducted from March to September 2025 at Anugerah Medical Center and Yukum Medical Center Hospital Lampung. Inclusion criteria included cesarean patients aged ≥18 years, with written consent, ERACS, and conventional eligible. Exclusion criteria were complications, previous surgery, and chronic medical conditions. The ERACS group had a mean length of stay of 1.10 days (86.3% stayed 1 day), while the conventional method had a mean length of stay of 2.20 days (78.4% stayed 2 days). The test showed p-value of 0.000, indicating a significant difference between the two groups. The ERACS method proved more effective in reducing length of stay, which is expected to improve hospital quality and performance. This study contributes to health practice by advocating for the adoption of ERACS protocols, which may lead to better resource allocation and more efficient healthcare delivery in the context of increasing cesarean rates.